Awareness and use of massive open online courses among library and information science professionals in Eswatini. Issue 4 (1st December 2020) - Tsabedze, Vusi; Tella, Adeyinka
Abstract: Massive Open Online Courses (MOOCs) is gaining pace in this 21st century and has become a new trend in the enrollment of academic programmes across the globe. MOOCs are online tools that support training of participants free of costs. However, it awareness and use among Library and Information Science professionals in Eswatini have not been considered. This study therefore examined Library and Information Science professionals' level of awareness and extent of usage of MOOCs. The study was carried out in Eswatini with a total of 41 respondents. A questionnaire was used for data collection. Collected data were analysised using despcriptive statics including frequency counts, percentages, mean and standard deviation. The study developed five objectives and the findings revealed that MOOC's use is still at the infant stage due to inadequate awareness and infrastructure for internet connectivity. The study, therefore, recommends methods for improvement for the blended and improved learning experience.